"Professional Helper" or "Helping Professional?" The Patient–Physician Relationship in the Chronic Pain Setting, With Special Reference to the Current Opioid Debate. Issue 2 (2016) - Bäckryd, Emmanuel
Abstract : Abstract: There seems to be a strong cultural expectation among patients for effective pain relief. As a result, physicians often find themselves trying to bridge the gap between the chronic pain patient's expectations and harsh biomedical reality. The typology of Emanuel and Emanuel of four models for the patient–physician relationship is used in this article as a conceptual tool to examine the possible roles of physicians in the context of chronic noncancer pain. Their typology is reconceptualized as a "pathway" along which the physician is able to walk more or less far, starting from the "information" end of the path. The other end of the pathway is "caring deliberation." I then propose that, in pain medicine today, consumerism is a powerful incentive for physicians to stay at the information end of the spectrum. Against this background, I discuss the current opioid epidemic in the United States and the need for what has been called a new medical professionalism. I conclude by challenging educators involved in pain medicine continuing professional development to not only design adequate biomedical–educational programs, but also consider issues like professionalism, personal development, critical self-reflection, and the ethics of engaging in caring deliberation with chronic pain patients.